Global, regional and national patterns and gender disparity of intraocular foreign bodies from 1990 to 2021 - Yi Shan; Fei Chen; Dong Xu; Wenqing Jia; Shangchen Hao (Frontiers in Public Health, 2025)
PurposeTo describe and evaluate the gender and socioeconomic disparities in the global burden of intraocular foreign bodies (IOFBs) from 1990 to 2021.MethodsGender-specific prevalence and disability-adjusted life years (DALYs) of IOFBs by year, age, geography and socioeconomic status were extracted from the Global Burden of Disease Study 2021. We used the Wilcoxon signed rank test and linear regression analysis to research the relationship between the age-standardized DALYs rate and gender difference (males minus females) and Socio-demographic Index (SDI).ResultsThe total all-age prevalence and DALYs due to IOFBs rose by 41.9 and 35.5%, respectively, from 1990 to 2021, and the age-standardized prevalence and DALYs rates decreased by 15.2 and 19.6%. The IOFBs burden was greater among middle-aged and older adult men, especially in 45–49 years. The burden of IOFBs was concentrated in countries of Western Europe, East Asia, High-income North America and Southern Latin America. The age-standardized DALYs rates of males were significantly higher than those of females in all five SDI groups (p < 0.001) in 2021. Pearson’s correlations (r = 0.3093, p < 0.001) and linear regression (Y = 4.850*X − 1.857) revealed a significant positive association between gender differences and SDI. The increase in the all-age DALYs of IOFBs was lowest compared with other eye diseases in GBD 2021. The IOFBs had the greatest gender-related differences compared with other eye disorders.ConclusionThe burden of IOFBs is higher among men in terms of age, region, and SDI categories. Male workers in regions with higher SDI should receive more attention. Measures are needed to improve eye protection and reduce eye injuries among males in the workplace.